Evaluation of the impact of an augmented model of The Productive Ward: Releasing Time to Care on staff and patient outcomes: a naturalistic stepped-wedge trial. Issue 1 (26th March 2020) - Williams, Brian; Hibberd, Carina; Baldie, Deborah; Duncan, Edward A S; Elders, Andrew; Maxwell, Margaret; Rattray, Janice E; Cowie, Julie; Strachan, Heather; Jones, Martyn C
Abstract : Background: Improving the quality and efficiency of healthcare is an international priority. A range of complex ward based quality initiatives have been developed over recent years, perhaps the most influential programme has been Productive Ward: Releasing Time to Care. The programme aims to improve work processes and team efficiency with the aim of 'releasing time', which would be used to increase time with patients ultimately improving patient care, although this does not form a specific part of the programme. This study aimed to address this and evaluate the impact using recent methodological advances in complex intervention evaluation design. Method: The objective of this study was to assess the impact of an augmented version of The Productive Ward: Releasing Time to Care on staff and patient outcomes. The design was a naturalistic stepped-wedge trial. The setting included fifteen wards in two acute hospitals in a Scottish health board region. The intervention was the Productive Ward: Releasing Time to Care augmented with practice development transformational change methods that focused on staff caring behaviours, teamwork and patient feedback. The primary outcomes included nurses' shared philosophy of care, nurse emotional exhaustion, and patient experience of nurse communication. Secondary outcomes covered additional key dimensions of staff and patient experience and outcomes and frequency of emergency admissions for same diagnosis within 6 months of discharge. Results: We recruited 691 patients, 177 nurses and 14 senior charge nurses. We found statistically significant improvements in two of the study's three primary outcomes: patients' experiences of nurse communication (Effect size=0.15, 95% CI; 0.05 to 0.24), and nurses' shared philosophy of care (Effect size =0.42, 95% CI; 0.14 to 0.70). There were also significant improvements in secondary outcomes: patients' overall rating of ward quality; nurses' positive affect; and items relating to nursing team climate. We found no change in frequency of emergency admissions within six months of discharge. Conclusions: We found evidence that the augmented version of The Productive Ward: Releasing Time to Care Intervention was successful in improving a number of dimensions of nurse experience and ward culture, in addition to improved patient experience and evaluations of the quality of care received. Despite these positive summary findings across all wards, intervention implementation appeared to vary between wards. By addressing the contextual factors, which may influence these variations, and tailoring some elements of the intervention, it is likely that greater improvements could be achieved. Trial registration number: UKCRN 14195.